Acute Abdomen due to Small Bowel Obstruction by Ascaris Lumbricoides in an 18‐Year‐Old Male: A Case Report and Review of the Literature - Seyed Abbas Fatemiyoun; Farzad Rafiei; Seyed Shahab Adin Sheikhalishahi (Clinical Case Reports)
ABSTRACT Intestinal obstruction caused by Ascaris lumbricoides (AL) is rare but clinically significant, particularly in endemic regions. We report an 18‐year‐old Afghan male who presented with a two‐month history of intermittent right lower quadrant pain, worsening over the past week with anorexia, constipation, nausea, and fatigue. Examination revealed generalized abdominal tenderness, involuntary guarding, and silent bowel sounds, suggesting an acute abdomen. Initial diagnosis was complicated appendicitis. After stabilization, laparotomy revealed a small bowel obstruction caused by a mass of AL, which was relieved via enterotomy and bowel repair. An incidental appendectomy was performed. Postoperatively, the patient was treated with albendazole and mebendazole. Bowel function returned by postoperative day three, and he was discharged on day five in stable condition. At one‐week follow‐up, he was asymptomatic with no complications. This case highlights the diagnostic challenges of parasitic infections, especially in non‐endemic areas, and emphasizes the importance of early imaging, timely surgical intervention, and comprehensive management. Clinicians should maintain a high index of suspicion for parasitic causes in bowel obstruction cases, particularly in endemic populations, to ensure prompt diagnosis and optimal outcomes.